Educação e força de trabalho em uma economia primário-exportadora: o panorama das ocupações para os egressos do ensino médio da microrregião de Capanema-Pr - Silva, Luciano Edison da (2020)
An important period for youth, when the labor market is on their radar screen, the last stage of basic education has become the big bottleneck, compromising a decent insertion in the labor market. This passage has been frustrated by high rates of unemployment and precariousness, which not even the highest schooling has been able to reverse. Anchored in data collected from websites such as ILO, IBGE, IPEA, IPARDES, MEC, MTE, DIEESE and analyzed from a broad theoretical framework on the subject, the results show that the economic process of deindustrialization and reprimarization of the economy, as well as its historical orientation toward low technological activity, has put little pressure on education. In this sense, the main objective of this research is to present an overview of jobs for high school graduates, based on the analysis of occupations and education available from 2007 to 2017 in the Microregion of Capanema, State of Paraná. The scenario is not at all encouraging, since not only has there been a reduction in admissions of young people and in wage premium, but also in highly complex occupations. Located in the southwest of Paraná, this region has reproduced a similar movement, which does not escape the national conjuncture. Education, even expanding the offer in several types of education (mainly professionalizing), has regressed in indicators in an alarming way, in tune with the economic structure that, at the same time, registers the increase of job offer, but for occupations of low complexity.